Preliminary Design of Electric Linear Actuator for Hospital Bed Domestic Product - Setiyo Hermawan; Heru S.B. Rochardjo (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2022)
Nowadays, the need for linear actuator as a component of a hospital bed is increasing due to the growing needs of electric bed. The function of this component is to adjust the form of the bed for the patient’s comfort. However, the producers of the local hospital bed mostly rely on foreign products. To reduce the production cost, an effort was made to design a low cost yet functional electric linear actuator. The actuator using basic components, consists of a DC motor, transmission, and screw mechanism. Stainless steel pipe with outer diameter of 26 mm was used for the body of the actuator. The performance of the actuator was tested by applying gradual loading with variations on the stroke. It was shown that the the actuator works well in varying loads from 0 to 150 kg with varying stroke from 0 to 19 cm.